Extraction of Cellulose from Kepok Banana Peel (Musa parasidiaca L.) for Adsorption Procion Dye - Poedji Loekitowati Hariani; Fahma Riyanti; Riski Dita Asmara (Molekul, 2016)
The aim of the research was to extract a cellulose from kepok banana peel (Musa parasidiaca L.) and application to removal Procion dye. The extracted cellulose was prepared by dewaxing process to releasing of lignin, bleaching and hemicellulose removal. The cellulose identified by FTIR and SEM-EDS. The efficiency of the cellulose to adsorp Procion dye was evaluated by variation in the initial concentration of dye (5, 10, 15, 20, 25, 30, 35, 40, 45 and 50 mg/L), solution pH (3, 4, 5, 6, 7, 8 and 9), and the contact time (15, 30, 45, 60, 75 and 90 minutes) at room temperature. The result showed that FTIR spectra of cellulose from kepok banana peel were similar with FTIR spectra of standardcellulose. The morphology of cellulose more homogenous than kepok banana peel powder. It was observed that the optimum adsorption of Procion dye by cellulose was on the initial concentration of 30 mg/L, pH solution of 5 and contact time within 30 minutes. The obtained result that cellulose has removal percentage to adsorp Procion dye more higher than kepok banana peel powder. The adsorption equilibrium showed the Langmuir isotherm was described well for adsorption process (R2 = 0.991) than Freundlich isotherm (R2 = 0.922).